UMPSA organises 2023_2024 Mentoring Appreciation Ceremony - Muhammad Syamim Aiman, Abd Hamid (UMPSA, 2024)
PEKAN, 3 September 2024 – The Sejahtera Centre, Student Affairs and Alumni Department, together with the Human Resource Development Division of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) recently hosted a Mentoring Appreciation Ceremony for the 2023/2024 Session.